Policy Mixes and their Alignment over Time: Patching and stretching in the oil sands reclamation regime in Alberta, Canada. (18th October 2017) - Rayner, Jeremy; Howlett, Michael; Wellstead, Adam
Abstract: When, why and how do policy mixes change and evolve? Much of the contemporary interest in such mixes is focused on distinguishing simple policies from more complex policy mixes, evaluating the relationships between single and multiple policy tools within a mix, and developing criteria to assess the likely performance of particular mixes. These are important and necessary analytical tasks. However, another required step in understanding policy mixes is to understand how and why mixes evolve and change over time and to determine whether any changes are an improvement. In this paper, we analyse the development of a complex policy mix in the case of reclamation and remediation of the Alberta oil sands from an earlier 'simple goal, single instrument' policy regime to a more complex one. This case study reveals the presence of at least two dynamic processes at work in policy mix development, with significant implications for the nature of the changes that result from them. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment